Acral hyperpigmented macule suspicious of malignant melanoma. Issue 3 (4th January 2022) - Kado, Soichiro; Kamiya, Koji; Maekawa, Takeo; Komine, Mayumi; Murata, Satoru; Ohtsuki, Mamitaro
Abstract : Dermoscopy is a noninvasive useful tool to differentiate malignant melanoma from other benign or malignant skin lesions. One of the recent advances in dermoscopy is the significance of parallel ridge pattern, which has 99% specificity in detecting malignant melanoma on the acral volar skin. Here, we report a case of acral hyperpigmented macule suspicious of malignant melanoma.